Going infinite : the rise and fall of a new tycoon - Lewis, Michael (Michael M.) (W.W. Norton and Company, 2023)
"When Michael Lewis first met him, Sam Bankman-Fried was the world's youngest billionaire and crypto's Gatsby. CEOs, celebrities, and leaders of small countries all vied for his time and cash after he catapulted, practically overnight, onto the Forbes billionaire list. Who was this rumpled guy in cargo shorts and limp white socks, whose eyes twitched across Zoom meetings as he played video games on the side? In Going Infinite Lewis sets out to answer this question, taking readers into the mind of Bankman-Fried, whose rise and fall offers an education in high-frequency trading, cryptocurrencies, philanthropy, bankruptcy, and the justice system. Both psychological portrait and financial roller-coaster ride, Going Infinite is Michael Lewis at the top of his game, tracing the mind-bending trajectory of a character who never liked the rules and was allowed to live by his own--until it all came undone"--